Design Strategy for State Islamic Universities (PTKIN) Towards Science and Technology Development In Indonesia - Abdul Fattah (UIN Mataram, 2016)
One of the issues most discussed in the arena of contemporary Muslim thought in the last few decades is about Islam and science. Muslim intellectuals provide diverse responses to these issues, particularly associated with the character of modern science and technology. Some people regard science and technology as something neutral and universal. While others assess the science and technology is not neutral, depending on its creator. Therefore, Muslims must be careful with science and technology from the West. Noteworthy together is a contemporary Muslim scholar realized that the only way to drink in the glory (golden age) of Muslims is through the mastery of science and technology. In terms of locality Indonesia, the expectations of many lay on the State Islamic Universities (UIN, IAIN, and STAIN), especially in the framework of the integration between Islam and science and to eliminate the dichotomy of science that has made Muslims excluded from the global science and technology arena.